Contralateral prophylactic mastectomy in the setting of breast cancer diagnosis and their insurance coverage in the United States. Issue 10 (15th September 2021) - Ha, Michael; Ngaage, Ledibabari M.; Klein, Marissa; Yang, Annie; Colohan, Shannon M.; Nurudeen, Suliat M.; Terhune, Julia H.; Slezak, Sheri; Rasko, Yvonne M.
Abstract: Background: Contralateral prophylactic mastectomy (CPM) is more common in the United States than the rest of the world. However, the benefit of this procedure is still under question in many breast cancer scenarios. CPM utilization in the United States is in part dependent on a patient's health insurance coverage of breast oncology surgery and any desired reconstruction. However, there are great discrepancies in the coverage provided by insurers. Methods: The authors conducted a cross‐sectional analysis of insurance policies for a CPM in the setting of diagnosed breast cancer. One hundred companies were selected based on their state enrollment and market share. Their policies were identified through a Web‐based search and telephone interviews, and their medical necessity criteria were extracted. Results: Of the 100 companies assessed, 36 (36%) had a policy for CPM. Within those, significantly more provided coverage than denied the procedure (72% vs. 25%, p  < 0.0001), with the remainder providing case‐by‐case coverage. Eleven criteria were identified from preauthorized policies, the most common prerequisite was breast cancer diagnosis under 45 years old ( n  = 9, 35%). Most policies did not differentiate between gender in their policies ( n  = 25, 69%), but of those that did, 100% ( n  = 11) provided coverage for men and women, with 82% ( n  = 9) requiring further criteria from the female patients. Conclusion: The coverage of CPM in the United States varies from complete denial to unrestricted approval. This may be due to conflicting reports in the literature as to the utility of the procedure. The decision to undergo this procedure must be taken with thoughtful consideration and the support of a multidisciplinary approach.